Pemberian Nasi Beras Merah (Oriza Nivara) dan Nasi Beras Hitam (Oriza Sativa L. Indica) terhadap Perubahan Kadar Glukosa pada Penderita Diabetes Melitus - Laode Ardiansyah; Nawawi Nawawi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effect of giving brown rice (Oryza nivara) and black rice (Oryza Sativa L. Indica) to changes in blood glucose levels in people with diabetes mellitus in Kendari City. This research method was carried out with a quasi-experimental design with a pre-post test design test. The results of the study on checking blood glucose levels before and after giving brown rice (Oryza nivara) and black rice (Oryza sativa L. indica) within one week obtained P-Value = 0.000 from P-Value <0.05, while in comparison between brown rice (Oryza nivara) and black rice (Oryza sativa L. indica) on changes in blood glucose in people with diabetes mellitus in Kendari City obtained P-Value = 0.19 from P-Value < 0.05. In conclusion, there is an effect of giving red rice (Oryza nivara) and black rice (Oryza sativa L. indica) on changes in blood glucose in people with diabetes mellitus in Kendari City. Keywords: Diabetes Mellitus, Blood Glucose Level, Black Rice, Brown Rice